Heat waves in Maribor between 1961-2018 - Žiberna, Igor; Ivajnšič, Danijel (Journal for Geography, 2018)
The article discusses the state and trends in the frequency of occurrence of heat waves, their duration and intensity in Maribor, based on data from the meteorological station Maribor-Tabor in the period 1961-2018. All three indicators show a clear positive trend. Particularly severe are trends in heat wave frequency and intensity. The average length of heat waves in Maribor is increasing as well, but the trend is less pronounced. Some local differences in the intensity of the urban heat island phenomenon during a heatwave period in Maribor were detected by applying remotely sensed data and the resulting land surface temperature variable from the Landsat 8 satellite.